A multiclade env–gag VLP mRNA vaccine elicits tier-2 HIV-1-neutralizing antibodies and reduces the risk of heterologous SHIV infection in macaques - Zhang, Peng; Narayanan, Elisabeth; Liu, Qingbo; Tsybovsky, Yaroslav; Boswell, Kristin; Ding, Shilei; Hu, Zonghui; Follmann, Dean; Lin, Yin; Miao, Huiyi; Schmeisser, Hana; Rogers, Denise; et al. (Nature medicine, 2021)
The development of a protective vaccine remains a top priority for the control of the HIV/AIDS pandemic. Here, we show that a messenger RNA (mRNA) vaccine co-expressing membrane-anchored HIV-1 envelope (Env) and simian immunodeficiency virus (SIV) Gag proteins to generate virus-like particles (VLPs) induces antibodies capable of broad neutralization and reduces the risk of infection in rhesus macaques. In mice, immunization with co-formulated env and gag mRNAs was superior to env mRNA alone in inducing neutralizing antibodies. Macaques were primed with a transmitted-founder clade-B env mRNA lacking the N276 glycan, followed by multiple booster immunizations with glycan-repaired autologous and subsequently bivalent heterologous envs (clades A and C). This regimen was highly immunogenic and elicited neutralizing antibodies against the most prevalent (tier-2) HIV-1 strains accompanied by robust anti-Env CD4 + T cell responses. Vaccinated animals had a 79% per-exposure risk reduction upon repeated low-dose mucosal challenges with heterologous tier-2 simian–human immunodeficiency virus (SHIV AD8). Thus, the multiclade env–gag VLP mRNA platform represents a promising approach for the development of an HIV-1 vaccine. An mRNA vaccine platform to prevent HIV-1 infection generated broadly neutralizing antibodies in non-human primates and protected some animals from infection, raising hope that optimization of this approach might lead to an effective HIV vaccine.